تدابير الضبط الإداري في مواجهة جائحة كورونا - سارة, قابوسة (جامعة الوادي.University eloued, 2021)
"ملخص الدراسة: - الضبط الإداري هو من أهم النشاطات الإدارية التي تساهم في استقرار المجتمع, و بالرغم من القيود التي ترد على الحقوق و الحريات الأساسية للمواطنين, فلا بد من الإقرار بأن سلطات الضبط الإداري تقوم بدور هام و فعال للحفاظ على النظام العام في الدولة, سواء في الظروف العادية أو الاستثنائية, على غرار الظروف الصعبة و غير المسبوقة التي يعيشها العالم من جراء تفشي وباء فيروس كورونا. و بعد إنتشار جائحة كورونا – كوفيد 19- في الجزائر وتهديدها للنظام العام سارعت مختلف الهيئات الضبطية إلى إتخاذ التدابير الضرورية للحد من إنتشارها, على الرغم من تقييدها للحقوق و الحريات إلا أنها هدفها الأوحد هو الحفاظ على الصحة العامة كواحدة من ركائز أمن المجتمع إذ يقع على عاتقها مسؤولية الحفاظ على المجتمع خاليا من الأمراض المعدية و وقايته منها بشكل فعال. "" Summary of the study: Administrative control is one of the most important administrative activities that contribute to the stability of society, and despite the restrictions imposed on the basic rights and freedoms of citizens, it must be recognized that the administrative control authorities play an important and effective role in maintaining public order in the state, if in normal or exceptional circumstances. Similar to the difficult and unprecedented circumstances that the world is experiencing as a result of the outbreak of the Corona virus epidemic. After the spread of the Corona-Covid-19 pandemic in Algeria and its threat to public order, the different police forces rushed to take the necessary measures to limit its spread, despite their restriction of rights and freedoms, but their only goal is to preserve public health as one of the pillars of society's security, as it bears the responsibility to preserve society is free from infectious diseases and effectively protected from them. "
ماستر قانون إداري
Keywords: الضبط الإداري, الحقوق والحريات, سلطات الضبط الإداري, فيروس كورونا, الصحة العامة.; "Administrative control, rights and freedoms, administrative control authorities, Corona virus, public health. "